2022
DOI: 10.1177/07067437221140384
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in Primary Care among People with Schizophrenia in Ontario, Canada, During the COVID-19 Pandemic

Abstract: Objective To investigate how primary care access, intensity and quality of care changed among patients living with schizophrenia before and after the onset of the COVID-19 pandemic in Ontario, Canada. Methods This cohort study was performed using primary care electronic medical record data from the University of Toronto Practice-Based Research Network (UTOPIAN), a network of > 500 family physicians in Ontario, Canada. Data were collected during primary care visits from 2643 patients living with schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
2
Order By: Relevance
“…One study from Canada compared monitoring rates of LDL and hemoglobin A1C (among other measures) and found a 10% decrease in monitoring rates for both items from pre-to postpandemic care. 8 Pre-pandemic rates of these measures were between 43% and 51%, which were considerably less than the phase 1 rates of over 60% seen in this study. A pre-pandemic study conducted in New Zealand measured primary care monitoring rates similar to phase 1, observing rates of weight (82%), lipids (66%), and A1C (70%) in their sample.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…One study from Canada compared monitoring rates of LDL and hemoglobin A1C (among other measures) and found a 10% decrease in monitoring rates for both items from pre-to postpandemic care. 8 Pre-pandemic rates of these measures were between 43% and 51%, which were considerably less than the phase 1 rates of over 60% seen in this study. A pre-pandemic study conducted in New Zealand measured primary care monitoring rates similar to phase 1, observing rates of weight (82%), lipids (66%), and A1C (70%) in their sample.…”
Section: Discussioncontrasting
confidence: 71%
“…Published studies in the medical literature do provide some insight regarding metabolic monitoring of antipsychotics in primary care settings, both pre‐pandemic and after it began. One study from Canada compared monitoring rates of LDL and hemoglobin A1C (among other measures) and found a 10% decrease in monitoring rates for both items from pre‐ to post‐pandemic care 8 . Pre‐pandemic rates of these measures were between 43% and 51%, which were considerably less than the phase 1 rates of over 60% seen in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…The continued elevated volumes of hospitalizations for psychotic disorders even as overall volumes returned to prepandemic levels may suggest that individuals living with these disorders face new challenges stemming from the pandemic. Though evidence from Ontario has found that primary care visits for these conditions in the first year of the pandemic were largely maintained virtually, 23 those unable to make the shift to virtual care may have had their continuity of care disrupted, 3 which has been found to be a predictor of future relapses. 24 Additionally, the possibility that those living with severe psychotic conditions would face challenges due to new norms requiring extended periods of isolation has been previously raised, given the known role of community social support in supporting care outside of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from Ontario, Canada found that people living with a diagnosis of schizophrenia experienced significant reductions in completion rates of blood pressure, haemoglobin A1C, LDL cholesterol and full blood counts in primary care settings during the pandemic, despite access to GPs being largely maintained through virtual appointments (Stephenson et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%